The effect of COVID-19 on the presentation of thyroid antibodies. Case report - Afrim Zeqiraj (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. In December 2019, the World Health Organization was notified about cases of pneumonia of unknown etiology originating in Wuhan, Hubei province, China. Hashimoto’s thyroiditis and other thyroid disorders including Graves’ disease affects almost 5 % of the general population. Hashimoto’s thyroiditis is a chronic disease in which the body interprets the thyroid gland and its hormone products as threats, therefore producing special antibodies that target thyroid cells, thereby destroying them. It may present with hypothyroidism or hyperthyroidism and with or without goiter. Basic questions in the consideration of a clinical case: what is COVID-19, and health complications? What concerns are related to pain in the front of the neck? How much has COVID-19 affected the occurrence of thyroid problems? Сase report. A 40-year-old man presented to the infectious disease clinic with a fever (37.9 °C), sore throat, body aches, and lethargy for 3 days on January 25, 2021. Due to the clinical features and the COVID-19 pandemic, a nasopharyngeal swab was used for sampling, and SARS-CoV-2 test was positive (mRNA in real time RT-PCR). On the 13th day, the patient’s general condition improved, but he complained of sore throat. On re-examination, we noticed a slight tenderness in the neck in the thyroid area. On thyroid ultrasound, a heterogeneous thyroid gland with ill-defined bilateral hypoechoic areas revealed subacute thyroiditis. The same patient presented to the infectious clinic with a fever (37.1 °C), sore throat, body aches and fatigue on June 28, 2022. After 5 days, the test for SARS-CoV-2 was negative, but, after one month of recovery, blood samples were analyzed to identify the functional state of the thyroid gland, and we obtained results with high values of thyroid-stimulating hormone. Conclusions. COVID-19 is a new disease for which larger-scale research is still ongoing, potential complications of COVID-19 and organ involvement are still being elucidated in the literature. Pain in the front of the neck, which can be combined with the upper part of the respiratory tract, especially in the conditions of COVID-19, should not be overlooked and requires further examinations. Subacute thyroiditis is a rare complication of COVID-19 that should be considered, especially in the progression of COVID-19 and the appearance of Hashimoto’s thyroiditis.